Plasmablastic lymphoma with an extra-oral location in a child with human immunodeficiency virus infection - Panja, Satarupa Mukherjee; Panja, Buddhadev (Journal of Pediatric Infectious Diseases, 2014)
Plasmablastic lymphoma (PBL) is a rare type of non-Hodgkin lymphoma frequently related to HIV infection. We report a case of PBL in a 7 year old female child with transfusion-acquired HIV infection on antiretroviral therapy (ART). The presentation was a swelling in the skull and cervical lymphadenopathy. CT scan revealed bony erosions with meningeal enhancement. The patient was started on chemotherapy and cranial irradiation but succumbed to death in 5 months. This is the first reported case of PBL involving the skull and meninges in a HIV-infected child.
Keywords: HIV; Plasmablastic lymphoma; skull